Antioxidant and toxicity studies on Octomeles Sumatrana (Datiscaceae) / Caroline Sunggip - Sunggip, Caroline (2009)
The antioxidant capacity and toxicity of the water soluble extract of the bark of Octomeles sumatrana (Datiscaceae), a medicinal plant known as Binuang by the Kadazandusun communities of Sabah, were investigated. The antioxidant capacity was evaluated by different methods such as photochemiluminesence, measurement of total phenolics, free radical (DPPH) scavenging activity and ferric reducing antioxidant power (FRAP). In addition, the inhibition of liver microsomal lipid peroxidation was assessed by the thiobarbituric acid reactive substance (TBARS) method.